2023
DOI: 10.3390/pharmaceutics15102437
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Siberian Pine Essential Oil Formulations Enhance Diabetic Wound Healing

Milica Nikolic,
Marijana Andjic,
Jovana Bradic
et al.

Abstract: This study aimed to develop novel topical formulations based on a natural component (0.5% of Siberian pine essential oil) and to assess its wound-healing capacity through macroscopic, histopathological, and biochemical examination. The phytochemical profile of Pinus sibirica essential oil (PSEO) and rheological analysis and safety potential of formulations were determined. The wound-healing effect was evaluated on an excision wound model in diabetic Wistar albino rats randomly divided into the following groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…cilicic had the strongest wound healing activity in both models used for evaluation (unlike the remainder of EOs, whose activity was negligible) [ 258 ]. Wound healing activity properties were also claimed for the fresh leaf EO of P. sibirica [ 259 ].…”
Section: Pharmacological Interest Of Pinaceae Eosmentioning
confidence: 99%
“…cilicic had the strongest wound healing activity in both models used for evaluation (unlike the remainder of EOs, whose activity was negligible) [ 258 ]. Wound healing activity properties were also claimed for the fresh leaf EO of P. sibirica [ 259 ].…”
Section: Pharmacological Interest Of Pinaceae Eosmentioning
confidence: 99%
“…Clinical studies have also demonstrated the potential of topical antioxidant application in improving diabetic wound healing, highlighting the translational relevance of targeting ROS. 486 , 487 …”
Section: Macrophages: Orchestrators Of Tissue Repair and Regenerationmentioning
confidence: 99%